The A Allele of the Single-Nucleotide Polymorphism rs630923 Creates a Binding Site for MEF2C Resulting in Reduced CXCR5 Promoter Activity in B-Cell Lymphoblastic Cell Lines - Mitkin, Nikita A.; Muratova, Alisa M.; Schwartz, Anton M.; Kuprash, Dmitry V. (Frontiers in Immunology, 2016)
Chemokine receptor CXCR5 is highly expressed in B-cells and under normal conditions is involved in their migration to specific areas of secondary lymphoid organs. B-cells are known to play an important role in various autoimmune diseases including multiple sclerosis (MS) where areas of demyelinating lesions attract B-cells by overexpressing CXCL13, the CXCR5 ligand. In this study, we aimed to determine the functional significance of single-nucleotide polymorphism rs630923 (A/C), which is located in cxcr5 gene promoter, and its common allele is associated with increased risk of MS. Using bioinformatics and pull-down assay in B-lymphoblastic cell lines, we showed that protective minor rs630923 “A” allele created functional binding site for MEF2C transcription factor. Elevated MEF2C expression in B-cells correlated with reduced activity of cxcr5 promoter containing rs630923 “A” allele. This effect that was fully neutralized by MEF2C-directed siRNA may mechanistically explain the protective role of the rs630923 minor allele in MS. Using site-directed mutagenesis of the cxcr5 gene promoter, we were unable to find any experimental evidence for the previously proposed role of NFκB transcription factors in rs630923-mediated CXCR5 promoter regulation. Thus, our results identify MEF2C as a possible mediator of protective function of the rs630923 “A” allele in MS.